A CONTROL METHOD FOR DRIVING DUAL PERMANENT MAGNET SYNCHRONOUS MOTORS FED BY SINGLE MATRIX CONVERTER - Yakut, Yurdagul Bentesen; Sunter, Sedat; Ozdemir, Mehmet (Univ Osijek, Tech Fac, 2017)
In this study, a control method is created to drive two parallel-connected permanent magnet synchronous motors fed by a single converter. Matrix converter used in this work provides ac-ac conversion in one stage. The matrix converter model and d-q model of dual PMSMs are performed in Matlab/Simulink. In industrial applications containing dual motors fed from a single converter, volume and weight of the drive system decreases, power electronics switches and other components are reduced and the installation cost decreases. Because of these advantages, many methods are being developed by researchers to control the dual motor drives. In this study, the motor control has been performed by using the average speed method. Control of dual permanent magnet synchronous motors with a single converter is implemented with ANFIS-based neural fuzzy controllers. All parameters of the motors are taken equal since two identical permanent magnet synchronous motors are considered. Two various operation conditions are investigated in the simulation. In the first case, one of the identical motors is operated on no-load, while the other one is operated with the rated load. In the second case, each motor is operated with various load torques varying with the time. Corresponding simulation results have been presented to show the performance of the drive system.
Metoda upravljanja pogonom sinhronih motora s dvostrukim trajnim magnetom napajanih pretvara?em s jednom matricom
Keywords: dual motor drives; matrix converter; neural fuzzy; PMSM; variable load; vector control